COVID-19–Related Trajectories of Psychological Health of Acute Care Healthcare Professionals: A 12-Month Longitudinal Observational Study - Abegglen, Sandra; Greif, Robert; Fuchs, Alexander; Berger-Estilita, Joana (Frontiers in Psychology, 2022)
The COVID-19 pandemic hit healthcare professionals (HCPs) hard, potentially leading to mental health deterioration. This longitudinal study investigated the 1-year evolution of psychological health of acute care HCPs during the COVID-19 pandemic and explored possible differences between high and low resilient HCPs. From April 2020 to April 2021, a convenience sample of 520 multinational HCPs completed an online survey every 3 months, up to five times. We used mixed linear models to examine the association between resilience and the variation of COVID-19-related anxiety, depressiveness, perceived vulnerability, and psychological trauma symptomatology. We demonstrated “u-shaped” trajectories for all mental health symptoms. We also explored differences in the abovementioned variables between front-line and second-line acute care HCPs. In contrast to HCP.s with lower levels of resilience (-1SD), those with higher levels of resilience (+1SD) showed increased COVID-19 anxiety and perceived vulnerability over time. Front-line and second-line HCPs differed in their depressiveness and psychological trauma variation during the 1-year analysis. High and average resilient second-line HCPs showed steeper depressiveness increases with time than high and average resilient front-line HCPs. Acute care HCPs reported their most elevated clinical symptoms of depressiveness (5–7%) and psychological trauma symptomatology (26–46%) in April 2020. During the first year of the COVID-19 pandemic, second-line HCPs with more resilience showed a steeper worsening of their depressiveness than more resilient front-line HCPs. HCPs with low resilience may benefit from interventions at the beginning of a pandemic, whereas HCPs with high resilience might benefit from resilience-enhancing interventions at later phases. Trial Registration The study protocol was pre-registered with the International Standard Randomised Controlled Trial Number (ISRCTN13694948) published (Fuchs et al., 2020).